The Importance of Geoheritage and Geo Top of the Charts in Environmental Studies (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
scientifically the following categories are excluded: biodiversity, geoheritage, geodiversity, geo tops, nature objects and others. They are important from the scientific, aesthetic, tourism, cultural points of view. The aim of environment sciences has to be to analyse the categories exhaustively and to determine the conditions of protection.